Correction: Hydrophobic durability characteristics of butterfly wing surface after freezing cycles towards the design of nature inspired anti-icing surfaces. - PLOS ONE Staff (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0188775.].